St Teresa of Ávila : her writings and life - O'Reilly, Terence; Thompson, Colin; Twomey, Lesley K. (Studies in Hispanic and Lusophone cultures ;, 2018)
At a time when women were effectively silenced in church, St Teresa of Ávila (1515-82) represents an extraordinary exception. Early struggles with her spiritual advisers gave way to an increasing confidence that she was inspired by God. She reformed the Carmelite Order she had entered as a young woman, and founded convents all over Spain, yet still found time to write a series of spiritual classics on the life of prayer which are characterized by a robust common sense, a directness of style, and a strong and positive vision of God’s love at work in individual lives. This collection of essays by leading scholars in Teresian studies covers topics in history, art history, literature, theology, and spirituality, in a fresh assessment of her significance five hundred years after her birth.